The Influence of Self-Confidence and Parent Attachment on Student Independence at Darul Qur'an Wal Irsyad Yogyakarta Islamic Boarding School - Agnestiti, Putri; Ardianti, Putri Mentari Ikrami; Sabila, Wizuray Vaya (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study uses a quantitative approach with multiple regression analysis. The research sample was 220 students taken by probability sampling technique, namely random sampling. In this study, the author uses a measure of independence obtained from the theory put forward by Noom, Meeus, and Decovic. The author adapts and modifies the data collection instruments, namely adolescence autonomy questionnaire (AAQ), Personal Evaluation Inventory (PEI), dan Inventory of Parent and Peer Attachment (IPPA). The results of this study show that self-confidence and parent attachment have a significant simultaneous influence on the independence of students at the Darul Qur'an Wal Irsyad Islamic Boarding School Yogyakarta. The overall self-confidence variable has a significant influence, where all significant aspects are academic, appearance, athletics, romantic, social, speaking, general, and mood. Meanwhile, parent attachment is divided into two variables, namely mother attachment and father attachment, each of which consists of three dimensions, namely trust, communication, and alienation. In the parent attachment variable, there are two dimensions that have a significant influence on the independence of students, namely communication and alienation of the mother attachment variable.